ANALISIS DAMPAK MOTIVASI DAN PROFESIONALISME TERHADAP KUALITAS AUDIT APARAT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH (Studi Empiris pada Pemerintah Kabupaten Cirebon) - Ida Rosnidah; Rawi '; Kamarudin ' (PEKBIS, 2012)
This research entitled is "The Impact of Motivation and Professionalism on the Auditquality of Inspectorate officers Financial Supervisory Areas (Empirical Studies inCirebon regency governments)." The purpose of this study was to examine theimpact of motivation and professionalism on audit quality. Common issues in thisresearch is the existence of audit findings that are not detected by the officers of theInspectorate as an internal auditor, but found by Badan Pemeriksa Keuangan (BPK)as the external auditor. This study has three variables, namely motivation andprofessionalism as independent variables and audit quality as dependent variables.Motivation variables were measured with four indicators of the level of aspiration,toughness, tenacity, and consistency. Variables measured with five indicators ofprofessionalism that is dedication to the profession, social obligations,independence, confidence in the profession, relations with other professions. Whileaudit quality is measured by three indicators of the process quality, quality results,and quality audit, follow-up audit. Method of this research is explanatory orConfirmation Research. The sampling data of this study using census techniques.The data analysis used is simple regression analysis and multiple regressions. Thepopulation chosen was the auditor in charge of the Inspectorate of Cirebon. Thesamples taken were 30 respondents. Based on the research that has been done, itcan be seen that the impact of motivation on audit quality is 12.6%, but notsignificant impact, professionalism impact on audit quality by 41.9% and significantlypositive. While, motivation and professionalism simultaneously impact on auditquality by 38.3%.